IMPLEMENTASI METODE PEMBELAJARAN INKUIRI PADA MATERI KIMIA RUMAH TANGGA TERHADAP PEMAHAMAN KONSEP SISWA SMP NEGERI I PULAU-PULAU ARU - Fatma Al Hamid (Molluca Journal of Chemistry Education (MJoCE), 2018)
Research aimed to know how the improvement of student concept understanding after process instruction using learning method inquiry. Research type deskriptive is choosen with design of learning package use one group pretest-posttest desing. Sample of this research are 33 students class VIII of SMP Negeri I Pulau-pulau Aru in academic year 2014/2015. Instrument of this research is test to examine student concept understanding, which is pretest and posttest. Data analyse with descriptive statistic show that the average of student pretest is 41,51%, the average of student postest is 85,45%, so the average gain of student concept understanding is 0,72 which show that the gain is avaliable in high gain cateogories. Based on data analyse and discussion, can be concluded that method learning inquiry is effective for use in instruction to improve student concept understanding in chemistry household matter